Stock Price Forecasting with the Weight Moving Average Method in Technology Sector Companies on the Indonesia Stock Exchange (IDX) - Syefira Ramadhani; Nurafni Eltivia; Nur Indah Riwajanti (PT. EQUATOR SINAR AKADEMIA, 2023)
This study aims to forecast the share price of the technology sector listed on the Indonesia Stock Exchange (IDX). We sampled 26 of the 34 technology companies listed on the IDX in 2022.Â The data used is secondary data from the official website of the Indonesia Stock Exchange, namely www.idx.co.id and finance.yahoo.co.id for 9 months, namely the period January â€“ September 2022. The results showed that the calculation of the Weight Moving Average (WMA) for the average value of the Absolute value of forecast error 16,374.70, and the value of the Absolute value of the Percentage of Error is 531.10%. The forecasting assessment method uses Mean Absolute Percent Error (MAPE). The resulting MAPE value is 3.02%. The highest MAPE score was Kioson Komersial Indonesia Tbk (KIOS) with a score of 5.99% while the lowest score was Sat Nusapersada Tbk (PTSN) with a score of 1.23%. From the results of MAPE for technology sector companies, it can be concluded that using the WMA Method and MAPE error valuation falls into the category of excellent forecasting ability in forecasting stock prices.